NANOTECHNOLOGY FOR DETECTION OF DISEASES CAUSED BY VIRUSES-CURRENT OVERVIEW - CHIPPA, SRILAXMI; SUVARNA, VASANTI (International Journal of Pharmacy and Pharmaceutical Sciences, 2021)
Nanotechnology is having a high impact on the development of a novel class of biosensors called nanobiosensors. This technology has utilized some extremely exciting elements for sensing phenomenon improvement. The utilization of nano-materials, nano-rods, nano-particles, nano-tubes have aided rapid, reliable reproducibility and its detection in a much better way. The unique properties of nanobiosensors and its varied applications have influenced biosensing research. Since longtime, nanobiosensors have been utilized worldwide for the diagnosis of diseases co-related with molecular detection of biomarkers. This paper highlights the use of such nanobiosensors for the detection of the virus, infections, fungal pathogens, Human Immunodeficiency Virus (HIV) related diseases such as Cardiovascular diseases (CDVs), Renal Arthritis (RA) through different techniques including electrochemical biosensing, optical biosensing, point of care-diagnostics etc.